EXPLORING ARCHITECTURAL ATTRIBUTES OF JAVANESE DWELLINGS: A CASE STUDY OF MR. MARYANTO’S CENTURY-OLD HOUSE - Setyadji, Kesit Himawan; Muqoffa, Mohamad; Marlina, Avi; Wulansari, Ayu Edhi Sri; Rachmanto, Rendy Adhi; Suyitno, Suyitno; Caroko, Novi; Yusuf, Mirza; Basuki, Basuki (Journal of Architecture&ENVIRONMENT, 2024)
This paper examines the architectural characteristics of Javanese houses and investigates the factors that influence their development and evolution. The study focuses on Mr. Maryanto’s house, a third-generation inhabitant of the house, which is estimated to be more than a century old. The research delves into the historical transformations of the house's structure and materials, particularly the “usuk” and “reng” replacements. Additionally, it explores the presence of unique ornamental features, such as the “naga” motifs on the “dhadha peksi”, which is unusual for rural houses. The paper analyzes the spatial layout and function of the rooms within the house, revealing the significance of factors like cultural traditions, economic conditions, and environmental adaptations in shaping Javanese house architecture.